PENGARUH PENGGUNAAN GAME ONLINE TERHADAP PERILAKU MAHASISWA UNIVERSITAS ISLAM RIAU PEKANBARU - Adrafika Adlis; W. E. Tinambunan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2014)
Online game or electronic game is a game played using net ( LAN or internet). This game has already achieved a great progress. Today's game is not like it was. High technology, especially internet connection makes this game can be played by more than 100 people in same time. This game makes university students distracted and change the way of students in interacting with others.The purpose of this research is to find out the influence of online game into attitude of Islamic university of Riau Pekanbaru's students and also to find out the influencing factor in using this such game among them. This is a quantitative survey. Data is collected using questionaire, documentation, and observation. To find out the influence, writer used simple linear regression analysis. X variable is game online, Y variable is students of UIR. There are 30 people acting as sample, taken based on criteria that meet research requirement, or accidental sampling. Data was processed SPSS verse 16.0.Result shows that there is influence of online game using into attitude of UIR Pekanbaru's students. It can be seen from data analysis; Y=140,11+0,6997 X with t hitung 6,212 bigger than t table 0,68304 and significancy level 0,700 smaller than a, got from N= 30 and a= 0,05. So, Ho is rejected and Ha is accepted because there is significant influence between online game using into students of UIR Pekanbaru. Factors that influence the attitude is technology, easy internet access, and environment.Keyword : Internet, Game online, Attitude